Hierarchical micromechanical modeling of the viscoelastic behavior coupled to damage in SMC and SMC-hybrid composites. (15th October 2018) - Anagnostou, Dimitrios; Chatzigeorgiou, George; Chemisky, Yves; Meraghni, Fodil
Abstract: The aim of this paper is to study, through a multiscale analysis, the viscoelastic behavior of glass reinforced sheet molding compound (SMC) composites and SMC-hybrid composites mixing two types of bundle reinforcement: glass and carbon fibers. SMC exhibit more than two distinct characteristic length scales, so that a sequence of scale transitions is required to obtain the overall behavior of the composite. An analytical procedure is used consisting of properly selected well-established micromechanical methods like the Mori-Tanaka (MTM) and the composite cylinders (CCM) accounting for each scale transition. After selecting a representative volume element (RVE) for each scale, the material response of any given length scale is described on the basis of the homogenized behavior of the next finer one. This hierarchical approach is appropriately extended to the viscoelastic domain to account for the time dependent overall response of the SMC composite material. The anisotropic damage has been introduced through a micromechanical model considering matrix penny-shape microcrack density inside bundles. The capabilities of the hierarchical modeling are illustrated with various parametric studies and simulation of experimental data for glass-based SMC composites.